2020
DOI: 10.1186/s12866-020-01729-3
|View full text |Cite
|
Sign up to set email alerts
|

The mismatch repair system (mutS and mutL) in Acinetobacter baylyi ADP1

Abstract: Background: Acinetobacter baylyi ADP1 is an ideal bacterial strain for high-throughput genetic analysis as the bacterium is naturally transformable. Thus, ADP1 can be used to investigate DNA mismatch repair, a mechanism for repairing mismatched bases. We used the mutS deletion mutant (XH439) and mutL deletion mutant (XH440), and constructed a mutS mutL double deletion mutant (XH441) to investigate the role of the mismatch repair system in A. baylyi. Results: We determined the survival rates after UV irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Certain rpoB mutations have rather complex consequences and often lead to different physiological characteristics. Different mutations in the rpoB gene may induce biofilm formation, impair surface-associated motility, or reduce virulence together with an increase in fitness costs [51][52][53]. In this study, we confirmed the mutated rpoB (G136D) resulted in a decrease in susceptibility to tigecycline when investigating a genetically reconstructed strain containing the rpoB mutation only.…”
Section: Discussionsupporting
confidence: 65%
“…Certain rpoB mutations have rather complex consequences and often lead to different physiological characteristics. Different mutations in the rpoB gene may induce biofilm formation, impair surface-associated motility, or reduce virulence together with an increase in fitness costs [51][52][53]. In this study, we confirmed the mutated rpoB (G136D) resulted in a decrease in susceptibility to tigecycline when investigating a genetically reconstructed strain containing the rpoB mutation only.…”
Section: Discussionsupporting
confidence: 65%
“…According to previous studies (LeClerc et al, 1996;Matic et al, 1997;Oliver et al, 2000;Eliopoulos and Blázquez, 2003;Jayaraman, 2009;Chu et al, 2017), mutations in the MutS, MutL, MutH, and UvrD proteins of the MMR system are the most important factors leading to hypermutability in bacteria. The mutation frequency in these strains ranged from 3.39 × 10 −4 to 5.46 × 10 −2 , which was increased by approximately 10 5 -to 10 6 -fold over the normal spontaneous mutation frequency of bacteria (LeClerc et al, 1996;Broaders et al, 2013;Zhou et al, 2020). In addition to high mutation frequency, MMR deficiency is associated with antibiotic susceptibility in hypermutators, and the hypermutators exhibit higher antibiotic resistance than normal bacteria (LeClerc et al, 1996;Oliver et al, 2002;Wilson et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Although many genetic deficiencies can lead to a hypermutable phenotype (LeClerc et al, 1996;Eliopoulos and Blázquez, 2003), hypermutation of bacteria is primarily caused by deficiencies in mutS, mutH, mutL, and mutU (uvrD) within the mismatch repair (MMR) system (LeClerc et al, 1996;Jayaraman, 2009;Veschetti et al, 2020). Mutations in these genes can result in increased mutation frequency and enhanced interspecies recombination (Verma et al, 2009;Zhou et al, 2020). Consequently, some genes encoding for antibiotic sensitivity and/or resistance, antibiotic uptake and/or efflux systems, or their regulatory factors can be altered in MMR-deficient bacteria (Eliopoulos and Blázquez, 2003;Fàbrega et al, 2009;Li et al, 2012;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampin is a synthetic derivative of natural products of the bacterium, with an inhibitory effect on beta-subunit of the RNA polymerase of prokaryotes and prescribed for gram-positive and gram-negative bacteria [59, 60]. Resistance to rifampicin (RIF) is mediated by mutations clustered in a small region of the rpoB gene [61, 62] which encodes the RNA polymerase β-subunit, or possibly by multidrug efflux pumps [59]. Previous studies confirmed mutation in the different amino acid sequences of rpoB protein mainly in 516, 526 and 536 mediated rifampin resistance in bacteria [60].…”
Section: Discussionmentioning
confidence: 99%